2014
DOI: 10.1136/injuryprev-2013-041006
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a home safety questionnaire used in a series of case-control studies

Abstract: ObjectiveTo measure the validity of safety behaviours, safety equipment use and hazards reported on a questionnaire by parents/carers with children aged under 5 years participating in a series of home safety case-control studies.MethodsThe questionnaire measured safety behaviours, safety equipment use and hazards being used as exposures in five case-control studies. Responses to questions were compared with observations made during a home visit. The researchers making observations were blind to questionnaire r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…14 Participants were asked to take part in a home safety study and not informed that the purpose of the home visit was to validate their previously completed questionnaire.…”
Section: Methodsmentioning
confidence: 99%
“…14 Participants were asked to take part in a home safety study and not informed that the purpose of the home visit was to validate their previously completed questionnaire.…”
Section: Methodsmentioning
confidence: 99%
“…In the validation study,28 only three poisoning exposures had at least moderate agreement (medicines kept in fridge (kappa=0.54), all household products stored at adult eye level or above (kappa=0.48) and having a kitchen safety gate (kappa=0.57)), and sensitivity and specificity were both ≥70% only for three exposures (all household products stored out of reach, all medicines and household products stored out of reach and use of kitchen safety gates). These relatively low levels of agreement may have resulted from parents reporting ‘socially acceptable’ responses, or changing prevention practices after their child's injury, after completing the study questionnaire or in anticipation of the home visit.…”
Section: Discussionmentioning
confidence: 99%
“…Over reporting may occur because repondents do not consider all levels of the home and because they may be unaware of indicators of alarm functionality (Hat eld et al 2006) While observed data may be the recognized gold standard, direct observations may not be feasible from a resource or time perspective. Self reported smoke alarm information is still useful (Stepnitz et al 2012) but data quality could potentially be improved by asking questions in a manner which causes respondents to think more deliberately about their homes and actions (Chen et al 2003;Watson et al 2014) The goal of the research presented here is to compare two self-reported measurement options to determine how to enhance the accurate reporting of the presence and functionality of smoke alarms. As part of a larger study on child home safety, we compared a Brief Form and an Extended Form of questions about smoke alarm status.…”
Section: Introductionmentioning
confidence: 99%